Numerical investigation of oblique impact behavior of a helmeted headform on a windshield considering failure. (February 2022) - Gao, Wei; He, Xiaoqiang; Wang, Jiawen; Feng, Y.T.; Wang, Chengyong
Abstract: A helmet, usually comprised of a composite shell, a foam liner and a chin strap, plays an important role for human head protection. Windshield glazing is a sandwiched structure which generally consists of two soda-lime glass layers bonded by a polyvinyl butyral (PVB) interlayer. In a motorcycle-vehicle accident, the rider's head wearing a helmet (i.e. so-called helmeted head) frequently collides onto the windshield laminated glass of a vehicle along an oblique direction. Such an oblique collision commonly results in head injury, helmet failure and windshield fracture. To model the oblique collision, the validated windshield model with the intrinsic cohesive zone model is adopted for the glass fracture and glass-PVB debonding, while an existing helmet model is employed with a continuum damage method and a crushable foam model for simulating the failure of the composite shell and the foam liner. Then, different impact velocities, foam liners with different densities, impact angles and headform postures are considered to thoroughly investigate their effects on the headform response and energy absorption performance of the helmet during the oblique collision. The simulation results show that a larger density or stiffer foam liner absorbs less energy and causes a larger maximum acceleration; and a composite liner has a better comprehensive performance than a single uniform liner, while the helmet posture has small effects on headform response and energy absorption. Highlights: Windshield and helmet failure is considered in their oblique impact process. Larger density liner absorbs less energy, and causes larger maximum acceleration, RIC. Composite liner has a better comprehensive performance. Larger impact angle causes much higher linear acceleration, HIC and HIP values. Helmet posture has small effects on headform response and helmet energy absorption.